Some Indices of Erythropoiesis System of Rats after Partial Hepatectomy and Transplantation of Cryopreserved Embryonic Liver Cells - Moiseyeva, N. N.; Rozanova, E. D.; Mazur, S. P.; Petrenko, A. Yu. (Problems of Cryobiology and Cryomedicine, 2002)
The authors studied the content of fetal and total hemoglobin in blood of rats after 70%-hepatectomy and transplantation of cryopreserved human embryonic liver (HEL) cells. Partial hepatectomy leads to a decrease in the content of total hemoglobin in ratsâ€™ blood during experiment and increasing of fetal hemoglobin level by the 3rdÂ day. After transplantation of cryopreserved HEL cells the content of total hemoglobin markedly exceeds the results in partially hepatectomised rats without transplantation by the 1stÂ and 2ndÂ day, and the level of fetal hemoglobin during this period decreased in 1.5 times. The transplant was identified in histological sections of liver and spleen from partially hepatoectomised rats with the method of fluorescent microscopy usingÂ monoclonal antibodies, labelled with fluorescent dye CD45-FITC.